Analisa Penerapan Prinsip Ekonomi Islam pada Aplikasi Digital Perdagangan Fisik Emas - Fahad, Sultan; Arasy Fahrullah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to investigate the outcomes of applying Islamic economic principles to digital gold trading on the MetalGO app. The study employed a qualitative research method with a descriptive approach, supplemented by descriptive quantitative methods involving interviews with four key informants: Islamic economists, app developers, and two users. Data collected included both primary (interview narratives) and secondary (literature review) sources, which were analyzed using qualitative and descriptive analysis techniques. The findings indicate that MetalGO is compliant with Islamic principles in its online gold trading operations, allowing users to purchase gold according to Shariah law. The app enables users to acquire physical possession of gold starting from 10,000 units, which can be delivered to their specified address upon request. Despite being an online gold trading platform, MetalGO adheres to Islamic economic principles such as Ekonomi Illayah, Ekonomi Rabbaniyah, and sma’ or asma’ wa sifat.